A Two-Stage Assessment of the Remote Engineering Lab VISIR at Al-Quds University in Palestine - Odeh, Salaheddin (2015)
Engineering labs are an essential part in engineering education since they provide practical knowledge for students, illustrate concepts and principles, and improve technical skills. Remote labs allow devices, equipment and instrumentations to be shared with other universities. Additionally, they relax time and space constraints, and are capable of being adapted to the pace of each student in case there was insufficient time in the laboratory. This paper describes an empirical study, which embeds two stages of assessment. In the first stage, we are concerned with finding out the level of flexibility when applying the engineering remote lab VISIR as a contemporary remote lab technology in the engineering faculty at Al-Quds University in Jerusalem in Palestine, and whether the engineering students will accept such technology to interact with in their future lab courses or not. In the second stage of the assessment study, a more in-depth comparative analysis will be carried out in order to have a categorization of VISIR in the landscape of the engineering labs such as hands-on and simulations. The three lab approaches will be compared with each other by means of an experimental testing based on assessment criteria that are in accordance with the fundamental course objectives of engineering instructional labs: student’s retention rate and satisfaction survey, as well as their performance.